Encyclopedia of Asian history - Embree, Ainslie Thomas (Scribner, 1988)
A collection of articles that survey the full scope of Asian history, discussing major historical events and periods from Bronze Age China to modern India, looking at the geography of the continent, profiling over 1,200 influential men and women, and examining aspects of Asian culture and society.